Influence of key parameters on the performance of a helium cryogenic system in refrigeration and liquefaction modes. (January 2022) - Xue, Rui; Yang, Shaoqi; Xie, Xiujuan; Pan, Wei; Xu, Xiangdong; Gong, Linghui
Highlights: An helium cryogenic system based on modified Claude cycle is selected for this study. Influence of key parameters on the performance of the cryogenic system is analyzed. Total UA of the heat exchangers is optimized using genetic algorithm. Guidance for selection between UA and specific energy consumption is supplied. The temperature deviation between calculated and experimental results is within 5%. Abstract: At present, medium-scale helium cryogenic system is commonly based on modified Claude cycle with two expanders in series. In this study, considering the minimum allowable heat exchanger temperature difference ( MHTDamd ), the influence of key parameters (including compressor discharge pressure ( Pcd ), temperature at the inlet of expander1 ( Tin-EXP1 ) and temperature at the inlet of Joule-Thomson valve ( Tin-JT )) on the system performance (including refrigeration capacity (RC)/liquefaction rate (LR), specific energy consumption (SEC) and total UA of the heat exchangers ( UAtotal )) of the helium cryogenic system is investigated and analyzed in refrigeration and liquefaction modes, respectively. The results show that in refrigeration and liquefaction modes, the optimal ranges of Pcd, Tin-EXP1, and Tin-JT are within 8 ∼ 10 bar, 30 ∼ 45 K and 5.2 K ∼ 7.2 K, respectively. Furthermore, the constraint relation between UAtotal and SEC is obtained. By using genetic algorithm (GA), it is found that keeping constraint SEC within 100%∼115% of the chosen SEC from the optimal range can achieve a relatively economic trade-offs between SEC and UAtotal . In the end, a comparison of T-S diagram obtained from design and experimental values in refrigeration and liquefaction modes is carried out, respectively. The maximum temperature deviation is within 5%, which verifies the accuracy of the calculation models. The optimized results in this study are also applicable to the same processes with mass flow rate of compressor lower than 100 g/s.